Goods Movement Robot Prototype Design with Wheel Arm System - Nur Iksan; Maulana, Mirza Arif; Nandika, Reza; Yani, Achmad; Panessai, Ismail Yusuf; Mohd Zulkefli, Nurul Akhmal (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
One of the uses of robotics technology that is developing is in the field of warehousing, with robots transferring vehicle goods used in the industrial world, especially in the warehousing section. The item transfer robot has 2 navigations, namely on the wheeled part, namely the robot can maneuver in all directions without the need to rotate the body of the robot (holonomic robot). Then one of the robots that is used quite often in the industrial world is the arm manipulator. Robots that have a physical shape like a human arm and a degree of freedom (Degree of Freedom). The transfer robot system is controlled remotely using an IoT-based smartphone using the ESP32 Wemos D1 R32 module as the robot's driving brain and ESP32-Cam as the robot's drilling visual. Several robot tests are carried out to ensure that the designed robot can run properly. From the results of functional testing, parts of the robot can run well. The robot can walk through commands from a smartphone, the gripper on the arm manipulator can grasp objects and the ESP32-Cam can display images to the smartphone.